Fragrances and essential oils - Groot, Anton C. de (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This second volume in an exciting and detailed series on contact allergens provides monographs of all 181 fragrances and 79 essential oils which have caused contact allergy / allergic contact dermatitis, including the indicators for fragrance allergy (fragrance mixes I and II and Myroxylon pereirae resin [Balsam of Peru]) and non-fragrance allergens in botanical products used in the perfume industry. The monographs present: Identification section; Contact allergy (general population, patients with dermatitis, case reports and case series); Cross-reactions; Patch test sensitization; Presence in products and chemical analyses; Other side effects (irritant contact dermatitis, photosensitivity, immediate-type reactions, systemic side effects) and more. Key Features: Presents monographs of all known fragrance chemicals and essential oils which have caused contact allergy / allergic contact dermatitis Provides a full literature review of relevant topics of allergenic fragrances and essential oils Identifies INCI and IUPAC names, synonyms, CAS and EC numbers, structural formulas, RIFM and Merck Index monographs, SCCS opinions, IFRA and EU restrictions and advises on patch testing Presents an alphabetical list of all synonyms indicating their INCI names Covers an extensive amount of information to benefit dermatologists, allergists, and non-medical professionals involved with the research, development and marketing of fragrances and essential oils
PrefaceAcknowledgmentsAbout the authorSECTION I RATIONALE AND DATA PROVIDED IN THIS BOOKChapter 1 IntroductionSECTION II FRAGRANCESChapter 2 Contact allergy to and allergic contact dermatitis from fragrances: a brief reviewChapter 3 Monographs of fragrance chemicals and extracts that have caused contact allergy / allergic contact dermatitisChapter 4 Monographs of chemicals not used as fragrances per se but present as allergens in botanical products used as fragrancesSECTION III ESSENTIAL OILSChapter 5 Essential oils: General aspectsChapter 6 Monographs of essential oils that have caused contact allergy / allergic contact dermatitisSECTION IV LISTS OF SYNONYMS AND INDEXChapter 7 List of synonyms of fragrancesChapter 8 List of synonyms of essential oilsIndex
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Dermatology; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic; Contact dermatitis; Allergy; Odors; Essences and essential oils